2000
DOI: 10.1074/jbc.m003424200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Serum Response Factor in the Depolarization Induction of Egr-1 Transcription in Pancreatic Islet β-Cells

Abstract: The results of the current studies define the major elements whereby glucose metabolism in islet ␤-cells leads to transcriptional activation of an early response gene in insulinoma cell lines and in rat islets. Glucose stimulation (2-20 mM) resulted in a 4-fold increase in Egr-1 mRNA at 30 min, as did the depolarizing agents KCl and tolbutamide. This response was inhibited by diazoxide and EGTA, indicating that ␤-cell depolarization and Ca Pancreatic islet ␤-cell mass can be regulated by multiple stimuli, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 50 publications
7
49
1
1
Order By: Relevance
“…The complete list of regulated genes is shown in Table 1S in the online appendix. Glucose-stimulated genes of diverse GO functions, described more fully below, included two immediate early genes previously identified as glucose responsive in islet ␤-cells, early growth response 1 (Egr1) (10,28), and an inhibitor of DNA binding 1 (Idb1) (29). Several other immediate early genes found to respond to mitogenic stimuli in other tissues (immediate early response 2 [Ier2] and 3 [Ier3] and inhibitor of DNA binding 2 [Idb2]) were also shown to respond to glucose treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete list of regulated genes is shown in Table 1S in the online appendix. Glucose-stimulated genes of diverse GO functions, described more fully below, included two immediate early genes previously identified as glucose responsive in islet ␤-cells, early growth response 1 (Egr1) (10,28), and an inhibitor of DNA binding 1 (Idb1) (29). Several other immediate early genes found to respond to mitogenic stimuli in other tissues (immediate early response 2 [Ier2] and 3 [Ier3] and inhibitor of DNA binding 2 [Idb2]) were also shown to respond to glucose treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In pancreatic ␤-cells, activation of expression of these IEGs was shown to depend on depolarization activation of voltage-gated Ca 2ϩ channels and subsequent influx of extracellular Ca 2ϩ . This resulted in activation of Ca 2ϩ -regulated kinases, including calmodulin-dependent kinase IV and protein kinase A, leading to phosphorylation and activation of several transcription factors (cAMP-responsive element binding pro-tein, serum response factor, and Elk-1) (9,10). The results of these experiments defined the rapid glucose-signaling pathways for a small number of IEGs whose transcription is rapidly activated by glucose, but the results now pose additional questions addressed by the current study.…”
mentioning
confidence: 99%
“…Altered Glucose-regulated Gene Expression in IRKD CellsPrevious studies have shown that glucose acutely alters early gene expression in islet ␤ cells and that these effects are mediated through depolarization, influx of extracellular Ca 2ϩ , and activation of kinase cascades that result in transcriptional activation (49,50). To examine the role of glucose-stimulated insulin secretion in this process, glucose-regulated early gene expression was examined in IRKD cells.…”
Section: Fig 2 Perturbed Insulin Signaling In Irkd Cellsmentioning
confidence: 99%
“…Additionally, it would be desirable to repeat these experiments in primary cultures of islets. Whereas early response genes have been extensively evaluated in response to glucose in primary cultures (49), gene expression profiles need to be repeated in primary cultures of islets from ␤IRKO animals (62).…”
Section: Con(e)mentioning
confidence: 99%
“…Loss of the cAMP/PKA response with mutation of the Egr-1 binding sites Pharmacological or hormonal activation of the cAMP/PKA signaling system has been reported to increase Egr-1 gene expression (mRNA and/or protein levels) in the ovary and in pheochromocytoma and insulinoma cell lines (Bernal-Mizrachi et al 2000, Espey et al 2000, Tai et al 2001. We hypothesized that cAMP-responsiveness of the LH gene may be mediated likewise by Egr-1 acting through previously identified Egr-1 ciselements in this gene.…”
Section: Activation Of the Camp/pka Signaling System Stimulates Lh Gementioning
confidence: 99%